BS ISO/IEC 15067-3-51. Information technology. Home Electronic System (HES) application model. Part 3-51. Framework of an On-Premises Narrow AI Engine for an Energy Management System using Energy Management Agents (12th November 2021) - British Standards Institution,
No abstract available